Análise da rede de relaç\~oes e sua influência nas políticas públicas de turismo - Joana Luiza Oliveira Alencar; Edgar Reyes Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This study analyses the influence of the actions undertaken by representatives of society in conveying demands for public policies. The object of the study is the National Tourism Council. Social network and field approaches were used with the goal of investigating how councilors engage with each other, and the results of their actions in the elaboration of tourism policies. The study makes studies 46 records of CNTur meeting minutes, recorded between 2003 and 2015. The analysis identified the demands presented, as well as the councilors who proposed, or supported them; this information served as a subsidy to the identification of the council's network structure. The results show that diversity among actors involved, external opposing actors, and propensity to contest pre-established rules are characteristics that favor the advancement of a demand. However, the existence of consensus in the council does not necessarily help in obtaining a favorable advancement of a demand.
Keywords: Z18; 330; State; Society; political field; network analysis; councius